Mouth-watering value-added products of onion and garlic - Gorrepati, Kalyani; Khade, Yogesh P. (Indian Horticulture, 2019)
Processing of onion and garlic into different value-added products wouldreduce the post-harvest losses and reduce the bulk and transportationcost. Different value-added products from onion and garlic are minimallyprocessed products, dehydrated flakes, powder, paste, pickle, oil etc.